2009
DOI: 10.1242/dev.035238
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP from the surrounding somatic cells regulates cyclic AMP and meiosis in the mouse oocyte

Abstract: Mammalian oocytes are arrested in meiotic prophase by an inhibitory signal from the surrounding somatic cells in the ovarian follicle. In response to luteinizing hormone (LH), which binds to receptors on the somatic cells, the oocyte proceeds to second metaphase, where it can be fertilized. Here we investigate how the somatic cells regulate the prophase-to-metaphase transition in the oocyte, and show that the inhibitory signal from the somatic cells is cGMP. Using FRET-based cyclic nucleotide sensors in follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
413
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(439 citation statements)
references
References 66 publications
9
413
0
5
Order By: Relevance
“…A high intra-oocyte cAMP concentration is produced endogenously within the oocyte by adenylate cyclases and constitutively active G-protein-coupled receptors (GPR) [2] and is generated by cumulus cells (CC) and transported to the oocyte via gap junctions [3,4]. Cyclic guanosine monophosphate (cGMP) diffuses from granulosa cells to the oocyte and inhibits cAMP degradation by inhibiting PDE3A [5,6]. In rodents, elevated cAMP concentrations activate protein kinase-A (PKA), followed by complex inhibitory mechanisms involving CDK1 -cyclin B kinase proteins suppressing activation of maturation promoting factor (MPF) and preventing meiosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high intra-oocyte cAMP concentration is produced endogenously within the oocyte by adenylate cyclases and constitutively active G-protein-coupled receptors (GPR) [2] and is generated by cumulus cells (CC) and transported to the oocyte via gap junctions [3,4]. Cyclic guanosine monophosphate (cGMP) diffuses from granulosa cells to the oocyte and inhibits cAMP degradation by inhibiting PDE3A [5,6]. In rodents, elevated cAMP concentrations activate protein kinase-A (PKA), followed by complex inhibitory mechanisms involving CDK1 -cyclin B kinase proteins suppressing activation of maturation promoting factor (MPF) and preventing meiosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, elevated cAMP concentrations activate protein kinase-A (PKA), followed by complex inhibitory mechanisms involving CDK1 -cyclin B kinase proteins suppressing activation of maturation promoting factor (MPF) and preventing meiosis [7][8][9]. In vivo, the pre-ovulatory surge of LH decreases cGMP concentrations in granulosa cells as well as oocytes [5,6]; the subsequent activation of PDE3A resulted in degradation of cAMP, activation of MPF, and resumption of meiosis (review; Conti et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies from a variety of laboratories have revealed that a drop in cAMP is a general feature of the initiation of oocyte maturation, including starfish and mouse oocytes (11,12). High cAMP levels in Xenopus oocytes appear to be mediated by elevated adenylyl cyclase, whereas inhibition of phosphodiesterase activity in mouse oocytes keeps cAMP high (13,14).…”
Section: Role Of Pka In Oocyte Maturationmentioning
confidence: 99%
“…There is a constitutively active adenylate cyclase in mammalian oocytes that produces cAMP (Mehlmann 2005). Recent research in mice has shown that cumulus cells, upon stimulation with natriuretic peptide precursor type C (NPPC), produce cyclic guanosine monophosphate (cGMP), which is transferred into the oocyte via gap junctions and inhibits PDE3 (Norris et al 2009;Zhang et al 2010). The combination of continuous cAMP production and little or no degradation of cAMP by PDE3 results in sufficient concentrations of cAMP within the oocyte to maintain meiotic arrest.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of continuous cAMP production and little or no degradation of cAMP by PDE3 results in sufficient concentrations of cAMP within the oocyte to maintain meiotic arrest. When the COC is removed from the follicle and the influence of NPPC, cGMP production by the cumulus cells is decreased, PDE activity within the oocyte increases, cAMP concentrations within the oocyte fall and the oocyte resumes meiosis (Norris et al 2009;Zhang et al 2010). Therefore, maintaining meiotic arrest in isolated COCs requires the use of chemicals that can maintain adequate concentrations of cAMP within the oocyte, either by stimulating production via adenylate cyclase or by inhibiting PDE activity, or both.…”
Section: Introductionmentioning
confidence: 99%